Avaliação de pontas de jato plano na deposição da calda de pulverização com diferentes combinações de plantas de feijão, Brachiaria plantaginea e Bidens pilosa - Rodrigues-Costa, A. C.P.; Costa, N. V.; Cardoso, L. A. [UNESP]; Pereira, M. R.R. [UNESP]; Martins, D. [UNESP] (FapUNIFESP (SciELO), 2010)
The objective of this study was to evaluate flat fan nozzle spray deposition on different combinations of the common bean plants, Brachiaria plantaginea and Bidens pilosa, in two volumes of application, with and without the addition of surfactant. Brilliant blue FDC -1 was used as tracer solution at the concentration of 500 ppm to evaluate the deposition. The treatments consisted of 7 combinations of plants: (common bean); (B. plantaginea); (B. pilosa); (common bean + B. plantaginea); (common bean + B. pilosa); (B. plantaginea + B. pilosa) and (common bean + B. plantaginea + B. pilosa). The experiment was arranged in a randomized block design. The flat fan nozzles XR 110015 VS and XR 11002 VS were evaluated, with volumes of application of 150 and 200 L ha-1, respectively, with and without the surfactant Silwet at 0.05% v v-1. After application, the plants were immediately collected and washed in 100 mL of distilled water for posterior tracer quantification in the spectrophotometer. The flat fan nozzles presented distinct behavior in droplet deposition on the species studied; the addition of a surfactant to the spray solution increased deposition uniformity, and contributed to the reduction of the volume application.
Evaluation of flat fan nozzles in spray deposition on different combinations of bean plants, Brachiaria plantaginea and Bidens pilosa
Keywords: Alexandergrass; Application volume; Beggarticks